Bio‐renewable polymers based on lignin‐derived phenol monomers: Synthesis, applications, and perspectives. Issue 5 (13th September 2022) - Yang, Weijun; Ding, Hui; Puglia, Debora; Kenny, Jose M; Liu, Tianxi; Guo, Jiaqi; Wang, Qingwen; Ou, Rongxian; Xu, Pengwu; Ma, Piming; Lemstra, Pieter Jan
Abstract: In recent decades, the continuous depletion of fossil fuels and the increasingly serious environmental issue have aroused wide attention on the development of biopolymers based on renewable biomass. Lignin is the second most abundant organic bio‐based macromolecule second to cellulose, and it can be widely found in plants. Furthermore, various phenol derivatives can be obtained by their depolymerization processes. The development of bio‐renewable polymeric materials originating from lignin‐derivative phenol monomers, such as vanillin, syringaldehyde, eugenol, vanillyl alcohol, vanillic acid, and ferulic acid, will not only valorize the bio‐sourced materials but also effectively reduce petroleum resource consumption and mitigate the environmental pollution. Therefore, an updated overview of the synthesis processes of these bio‐based polymers developed in the past decade, which includes both thermosets and thermoplastics such as epoxy, phenolic, polyimine, polybenzoxazine, polyurethane, and polyesters, are elucidated. In addition, the applications of these bio‐based polymers and their composites in flame‐retarded materials, degradable and reprocessable materials, dielectric materials, optoelectronic materials, as well as smart responsive materials are also intensively discussed. In line with the gradual development of synthesis technologies, we believe that derivatives of lignin will turn into one of the most promising materials to be considered for the preparation of high‐performance and functional bio‐based polymer materials. Abstract : Lignin, as an ideal "carbon" resource, is the second most abundant bio‐based macromolecule next to cellulose that can be widely found in plants, and various phenol derivatives such as vanillin, vanillyl alcohol, vanillic acid, eugenol, syringaldehyde and ferulic acid can be extracted by depolymerization processes from lignin. The synthesis processes of the bio‐renewable polymers based on lignin‐derived phenol monomers including both thermosets and thermoplastics such as epoxy, phenolic, polyimine, polybenzoxazine, polyurethane, and polyesters were well‐elucidated. In addition, the applications of these bio‐based polymers and their composites used for flame retarding materials, degradable and reprocessable materials, dielectric materials, optoelectronic materials, as well as smart responsive materials have been also intensively discussed.